Pathways for best practice diffusion: the structure of informal relationships in Canada's long-term care sector. (December 2017) - Dearing, James; Beacom, Amanda; Chamberlain, Stephanie; Meng, Jingbo; Berta, Whitney; Keefe, Janice; Squires, Janet; Doupe, Malcolm; Taylor, Deanne; Reid, Robert; Cook, Heather; Cummings, Greta; et al.
Abstract Background Initiatives to accelerate the adoption and implementation of evidence-based practices benefit from an association with influential individuals and organizations. When opinion leaders advocate or adopt a best practice, others adopt too, resulting in diffusion. We sought to identify existing influence throughout Canada's long-term care sector and the extent to which informal advice-seeking relationships tie the sector together as a network. Methods We conducted a sociometric survey of senior leaders in 958 long-term care facilities operating in 11 of Canada's 13 provinces and territories. We used an integrated knowledge translation approach to involve knowledge users in planning and administering the survey and in analyzing and interpreting the results. Responses from 482 senior leaders generated the names of 794 individuals and 587 organizations as sources of advice for improving resident care in long-term care facilities. Results A single advice-seeking network appears to span the nation. Proximity exhibits a strong effect on network structure, with provincial inter-organizational networks having more connections and thus a denser structure than interpersonal networks. We found credible individuals and organizations within groups (opinion leaders and opinion-leading organizations) and individuals and organizations that function as weak ties across groups (boundary spanners and bridges) for all studied provinces and territories. A good deal of influence in the Canadian long-term care sector rests with professionals such as provincial health administrators not employed in long-term care facilities. Conclusions The Canadian long-term care sector is tied together through informal advice-seeking relationships that have given rise to an emergent network structure. Knowledge of this structure and engagement with its opinion leaders and boundary spanners may provide a route for stimulating the adoption and effective implementation of best practices, improving resident care and strengthening the long-term care advice network. We conclude that informal relational pathways hold promise for helping to transform the Canadian long-term care sector.